Kidney re-transplantation in a child across the barrier of persisting angiotensin II type I receptor antibodies - Gold, Annika; Fichtner, Alexander; Choukair, Daniela; Schmitt, Claus P.; Süsal, Caner; Dragun, Duska; Tönshoff, Burkhard (Pediatric nephrology, 2021)
Approximately 20% of antibody-mediated rejection (ABMR) episodes in the absence of donor-specific antibodies against human leucocyte antigens (HLA-DSA) in pediatric and adult kidney transplant recipients are associated with, and presumably caused by, antibodies against the angiotensin type 1 receptor (AT1R-Ab). While the role of AT1R-Ab for ABMR and graft failure is increasingly recognized, there is little information available on the management of these patients for re-transplantation over the barrier of persisting AT1R-Ab.
Published online: 23 December 2020
Gesehen am 07.10.2021